METHODS AND CHEMICAL COMPOSITION OF THE PREPARATION OF MOLASSES FROM GRAPE FRUIT AND ITS USE IN MEDICINE - Usmanov Saminjon Olimovich (Journals Park Publishing, 2024)
This article provides information on the methods and chemical composition of making molasses from grapes, as well as its use in medicine.
Keywords: Grape Fruit, Vitamins, glucose, pectin, protein, carbohydrates.